Roles of the Mesenchymal Stromal/Stem Cell Marker Meflin in Cardiac Tissue Repair and the Development of Diastolic Dysfunction. Issue 4 (2nd August 2019) - Hara, Akitoshi; Kobayashi, Hiroki; Asai, Naoya; Saito, Shigeyoshi; Higuchi, Takahiro; Kato, Katsuhiro; Okumura, Takahiro; Bando, Yasuko K.; Takefuji, Mikito; Mizutani, Yasuyuki; Miyai, Yuki; Saito, Shoji; et al.
Abstract : Rationale: : Myofibroblasts have roles in tissue repair following damage associated with ischemia, aging, and inflammation and also promote fibrosis and tissue stiffening, causing organ dysfunction. One source of myofibroblasts is mesenchymal stromal/stem cells that exist as resident fibroblasts in multiple tissues. We previously identified meflin (mesenchymal stromal cell- and fibroblast-expressing Linx paralogue), a glycosylphosphatidylinositol-anchored membrane protein, as a specific marker of mesenchymal stromal/stem cells and a regulator of their undifferentiated state. The roles of meflin in the development of heart disease, however, have not been investigated. Objective: : We examined the expression of meflin in the heart and its involvement in cardiac repair after ischemia, fibrosis, and the development of heart failure. Methods and Results: : We found that meflin has an inhibitory role in myofibroblast differentiation of cultured mesenchymal stromal/stem cells. Meflin expression was downregulated by stimulation with TGF (transforming growth factor)-β, substrate stiffness, hypoxia, and aging. Histological analysis revealed that meflin-positive fibroblastic cells and their lineage cells proliferated in the hearts after acute myocardial infarction and pressure-overload heart failure mouse models. Analysis of meflin knockout mice revealed that meflin is essential for the increase in the number of cells that highly express type I collagen in the heart walls after myocardial infarction induction. When subjected to pressure overload by transverse aortic constriction, meflin knockout mice developed marked cardiac interstitial fibrosis with defective compensation mechanisms. Analysis with atomic force microscopy and hemodynamic catheterization revealed that meflin knockout mice developed stiff failing hearts with diastolic dysfunction. Mechanistically, we found that meflin interacts with bone morphogenetic protein 7, an antifibrotic cytokine that counteracts the action of TGF-β and augments its intracellular signaling. Conclusions: : These data suggested that meflin is involved in cardiac tissue repair after injury and has an inhibitory role in myofibroblast differentiation of cardiac fibroblastic cells and the development of cardiac fibrosis. Abstract : Supplemental Digital Content is available in the text.